A History of World Societies since 1450 : volume 2 - Wiesner, Merry E.; Ebrey, Patricia Buckley; Beck, Roger B.; Dávila, Jerry; Crowston, Clare Haru; MacKay, John P. (Bedford/Saint Martin's, 2017)
A History of World Societies provides a comprehensive overview of world history by sharing the cultural stories of global people -- all through a regional lens.